Mitigating of Financing Constraints in the Thai Banking System - Kengchon, Charl; Mahujchariyawong, Pimonwan; Vacharachaisurapol, Thanyalak (Thammasat Review of Economic and Social Policy, 2015)
The objective of this article is to analyze the development in mitigation of “financing constraints” in Thai banking system for both corporate and household sectors since the Asian Financial Crisis in 1997, which was a great turning point for the economic and banking system. The issue concerning financing constraints for business firms and households is considered as one of the most significant financial problems, causing the economy to be in a suboptimal equilibrium. This study found that the issues pertaining to financing constraints for business firms and household have been eased owing to several reasons. Banking innovations have been boosted due to changing competition landscape, and transformation of business goals under the restructuring of Thai laws and new economic conditions. Emergence of such innovations reflects right puzzles between risk management, operational procedures and IT, marketing and communications, as well as sales and service channels putting together, thereby assisting small and medium-sized enterprises (SMEs) and the household sector to gain better access to financing, either in dimension of quality, quantity and pricing. This is in line with the empirical evidence indicating that the changing cost of borrowing for entrepreneurs during the recent period was partly due to the development of financial system, competition among Thai banks and development of business banking innovations. All these factors assisted small firms which have enhanced their potential to access financial capital, closing the gap between them and bigger firms. Nevertheless, the different economic and financial conditions leave the issue open-ended for all the concerned institutions in determining the “appropriate” policy design to encourage the corporate and household sectors to access credits from banks under appropriate terms and conditions without affecting the long-term economic stability for the future challenges.